Sedimentary Facies, Palynology, and Organic Geochemistry of Eocene Kalumpang Formation in Lariang and Karama Areas, West Sulawesi, Indonesia - Rakhmat Fakhruddin; Nisa Nurul Ilmi; Edy Sunardi; Taufik Ramli; Agus Ardianto Budiman; Indra Nurdiana; Dzul Fadli (Directorate for Research and Community Services (LPPM) ITB, 2023)
The Kalumpang Formation was deposited in a delta plain setting. A Middle to Late Eocene age (Proxapertites operculatus zone) was inferred from palynological analysis, with a paleoenvironment in a coastal plain setting with a strong terrestrial influence. Samples from the Kalumpang Formation indicate a marginal to early mature stage for hydrocarbon generation. It is mostly composed of gas-prone to oil and gas-prone Type III kerogen facies. The biomarker character of both the rock and oil samples suggests a terrestrial origin, with a significant contribution of estuarine or bay organic material. The oil derives from a non-carbonate lithology, while the rock samples are from carbonate/calcareous shale origin. The abundance of oleanane compound and C30 resins suggests higher plant angiosperm input of Late Cretaceous or younger age for both the rock and the oil samples. The oil seep contains more abundant oleananes compared to the carbonaceous mudstone of the Kalumpang Formation. This suggests that the oil originated from more marine facies than the rock samples, which were deposited in a delta plain setting. This study demonstrated the agreement of depositional environment interpretation and age assessment between lithofacies, palynological, and organic geochemistry analysis.